2016
DOI: 10.1021/acs.jpcc.6b02821
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Iron–Sulfur Clusters with N2: Biomimetic Systems in the Gas Phase

Abstract: The active centers of the nitrogen-fixing enzymes nitrogenases comprise iron−sulfur clusters. The binding of the substrate N 2 to these clusters plays a fundamental role for the subsequent ammonia synthesis. However, due to the complexity of the natural system and the lack of suitable synthetic models, the interaction of N 2 with the iron−sulfur clusters remains largely elusive. In this contribution, we demonstrate the gas-phase preparation and investigation of the cationic Fe 2 S 2 + , Fe 3 S 3 + , and Fe 4 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
(121 reference statements)
2
24
0
Order By: Relevance
“…The end-on coordination mode is the most prevalent manner observed for N 2 adsorption on metal clusters . Previous investigations have elucidated that π back-donation of d- electrons from a single metal atom (the adsorption site) to π* orbitals of N 2 prevails in this binding mode (as shown in Scheme a). , In this work, an unprecedented interaction between the d – d bonding orbitals of dual iron sites and the π* orbitals of N 2 (Scheme b) in the end-on binding mode was disclosed to explain the superior reactivity of polynuclear iron–sulfur cluster anions Fe 5 S 2,3 – toward N 2 among the systematically investigated Fe x S y – ( x = 1–8, y = 0– x ). This is the first example to reveal that the dual iron site rather than a single Fe atom plays a crucial role to capture N 2 in the common end-on binding mode.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…The end-on coordination mode is the most prevalent manner observed for N 2 adsorption on metal clusters . Previous investigations have elucidated that π back-donation of d- electrons from a single metal atom (the adsorption site) to π* orbitals of N 2 prevails in this binding mode (as shown in Scheme a). , In this work, an unprecedented interaction between the d – d bonding orbitals of dual iron sites and the π* orbitals of N 2 (Scheme b) in the end-on binding mode was disclosed to explain the superior reactivity of polynuclear iron–sulfur cluster anions Fe 5 S 2,3 – toward N 2 among the systematically investigated Fe x S y – ( x = 1–8, y = 0– x ). This is the first example to reveal that the dual iron site rather than a single Fe atom plays a crucial role to capture N 2 in the common end-on binding mode.…”
mentioning
confidence: 70%
“…Dinitrogen is an abundant and easily accessible resource, but it is highly inert under ambient conditions. , The activation and functionalization of N 2 have therefore been a long-standing important research subject . In nature, nitrogen fixation is mediated by nitrogenase enzymes, in which N 2 reduction takes place at the active iron-based cofactors (FeMo/FeV/FeFe-cofactor) consisting of multinuclear iron–sulfur clusters in the weak-field sulfur-dominated environment. Spectroscopic studies have indicated that N 2 binds to the iron site of the FeMoco in an end-on configuration. Encouraged by the outstanding reactivity and unique structures of the nitrogenases, there has been intense research activity focusing on the iron–sulfur clusters with the ability to bind and reduce N 2 . ,− Despite remarkable achievements in the synthesis of complex iron–sulfur clusters in condensed-phase systems, examples involving N 2 binding to iron–sulfur clusters remain scarce. Only very recently, several synthesized mononuclear and multinuclear iron–sulfur complexes were reported to bind N 2 and induce the further functionalization of N 2 . ,, …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The combined use of experimental and theoretical techniques is a powerful methodology for the investigation of model reactions between N 2 and gas-phase species and has been used to reveal N 2 activation mechanisms in an unperturbed environment at a strictly molecular level. Specifically, the gas-phase species ,,, that possess the ability to cleave the NN triple bond under thermal collision conditions commonly involve the cooperation of more than one TM atom, for adsorbing and activating N 2 , with the exception of the previously reported Os/N 2 system . It is noteworthy that, although there are increasing reports on the N 2 activation mediated by gas-phase ions, the transformation of N 2 has rarely been reported. , Considering that the empty p orbital in boron is similar to the d orbital of transition metals and can, therefore, participate in efficient “donor–acceptor” processes upon interaction with N 2 , several B-based catalysts have been reported to be able to activate N 2 . Thus, boron-doped clusters probably are promising systems exhibiting a high reactivity toward N 2 activation.…”
mentioning
confidence: 99%